THE CONSERVATIVE ACCOUNTING MEASUREMENTS FROM THE PERSPECTIVE OF ACCOUNT IN FINANCIAL STATEMENT: Study on Manufacturing Sector In Indonesia - Murtianingsih, Murtianingsih; Oktavia, Sherly (LP2M Institut Teknologi dan Bisnis Asia Malang, 2023)
The purpose of this paper is to determine the implementation of conservative accounting from the perspective of financial statements which include tax incentives, debt contracts, and political costs as research variables in manufacturing companies. The research population is the manufacturing sector listed on the Indonesia Stock Exchange with a total of 178 companies and a purposive sample obtained by 78 companies with data collection techniques using documentation. Mulvariate regression techniques is the analytical tool used, and the results obtained indicate that tax incentives have a significant positive effect on conservative accounting. By contrast, debt contracts and political costs have no significant effect on conservative accounting. This paper provides encouragement to investors when evaluating financial statement changes related to conservatism, especially those relating to tax incentive accounts, debt convenant, and political costs.